The Electrochemistry of the corrosion of grinding media in Philippine sulfide ore slurries - Calata, Jesus Noel A.
Polarization measurements were conducted using Armco M-25 split grinding balls as working electrodes. A rotating electrode set-up was used. Tests for localized corrosion following the procedure in ASTM G 61 were a lso made. The calculated corrosion rates in supernatant solution from ore-tap water slurry were much higher. Average corrosion current densities of 20.6, 103.7, and 217.4 uA/cm2 were obtained for static, stirring and abrasion conditions, respectively. Stirring also resulted in more noble potentials while abrasion produced more negative potentials indicating an interaction between abrasion and corrosion. The addition of lime to the test solution also drastically reduced the corrosion rates. The corrosive rate was reduced by 82 percent for the abraded electrode while a corresponding reduction of 99.7 percent was realized in stirring conditions with a dosage of 500 g/ MT ore. Increasing the lime dosage did not produce any further significant reduction in corrosion rate. The tests for susceptibility to localized corrosion indicated a breakdown potential which is more noble by about 0.16V than the corrosion potential. The relative closeness of the breakdown potential to the corroosion potential suggests that the alloy is susceptible to pitting corrosion which may be obscured in actual grinding conditions because of the effect of abrasion of the grinding media surface.